Cryochemical synthesis of ultrasmall, highly crystalline, nanostructured metal oxides and salts - Trusova, Elena A.; Trutnev, Nikolai S. (Beilstein Journal of Nanotechnology, 2018)
In the present investigation, the cryochemical approach was used for the improved synthesis of nanocrystalline metal oxides (e.g., NiO, Fe2O3, CeO2) and NaNO3 salt. It was shown that the solutions and sols can be treated with a liquid nitrogen stream (−196 °C) to increase the powder dispersity by 3–18 times and to increase their specific surface area by an order of magnitude. The proposed approach also reduces the agglomeration of the nanoparticles, and at the same time, results in NiO, Fe2O3 and CeO2 crystallite sizes of less than 10 nm (quantum dot size regime). The diameter of NaNO3 salt crystallites could also be reduced to ≤50 nm by freezing in a liquid nitrogen atmosphere, which is a significant improvement over analogous salts obtained by traditional methods (average diameter 300–1000 nm). The characterization of the obtained nanopowders was carried out using X-ray diffraction, transmission electron microscopy, surface area measurements and diffusion aerosol spectrometry (DAS). It was determined that the addition of 3–15 wt % of NaF to the NaNO3 solution prior to its cryogenic treatment results in a further decrease in the particle size of the obtained crystalline salt. NaF creates a protective coating with a thickness of 2–3 nm on the surface of NaNO3 crystallites, preventing their association. The results obtained show that the cryochemical processing of the solutions during the preparation phase of production allows nanopowders to be obtained with improved morphological and textural characteristics without significant increase in technical development costs.
Keywords: cryochemical synthesis; cryosols; nanocrystalline metal oxides; nanostructured powders